2002
DOI: 10.1007/bf02376071
|View full text |Cite
|
Sign up to set email alerts
|

P-Type electronic conduction in CeO2- and LaGaO3-based solid electrolytes

Abstract: Abstract.Modifications of the e.m.f, and faradaic efficiency techniques, taking into account electrode polarization in the measuring cells, in combination with the use of electrodes having sufficiently high polarization resistances enable a precise determination of minor electronic contributions to the conductivity of solid electrolytes. These methods were used to determine the ptype conductivity of compositions based on La(Sr)Ga(Mg)O3_s (LSGM) and Ce(Gd)O2.s (CGO) at 900-1270 K. The oxygen ion transference nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 15 publications
3
67
0
Order By: Relevance
“…Therefore, the structure of the title materials in air was refined as cubic without deterioration of the refinement quality. This conclusion was confirmed by the neutron powder diffraction data at room temperature (26 , and/ or a greater level of structural disorder when gallium is introduced in the lattice. The ionic radius of Ga 3+ is smaller than that of high-spin Fe 3+ in the same coordination (27).…”
Section: Crystal Structuresupporting
confidence: 76%
“…Therefore, the structure of the title materials in air was refined as cubic without deterioration of the refinement quality. This conclusion was confirmed by the neutron powder diffraction data at room temperature (26 , and/ or a greater level of structural disorder when gallium is introduced in the lattice. The ionic radius of Ga 3+ is smaller than that of high-spin Fe 3+ in the same coordination (27).…”
Section: Crystal Structuresupporting
confidence: 76%
“…Upon first heating (annealing), the asdeposited films do not expand although they were kept successively at 100 (6 h), 350 (4 h), and 530 8C (2 h). It must be pointed out that, at 530 8C, the difference in the thermal expansion coefficients of the Si substrate and Ce 0.8 Gd 0.2 O 1.9 should have resulted in a compressive strain of: [20] DaDT ¼ ð11:5 À 3:1Þ Â 10 À6 ½K À1 Á 500 ½K ¼ 0:42% (2) where Da ¼ (11.5-3.1) Â 10 À6 K À1 Á is the average difference between the thermal expansion coefficients of Ce 0.8 Gd 0.2 O 1. 9 and Si (see Sec.…”
Section: Results and Preliminary Analysismentioning
confidence: 99%
“…5.5), which matches the value obtained for rapidly heated selfsupported Ce 0.8 Gd 0.2 O 1.9 films [5] and is close to the value reported in the literature for bulk Ce 0.8 Gd 0.2 O 1.9 (11.5 Â 10 À6 K À1 ). [20] This also agrees with data that indicates that no oxygen loss takes place in Ce 0.8 Gd 0.2 O 1.9 below 700 8C. [7] However, after the annealed films had been kept for over four months at room temperature, their out-of-plane lattice parameter spontaneously expanded by 0.78% (the d spacing of the (220) reflection increased from 1.925 to 1.940 (AE0.002) Å ) (Figs.…”
Section: Results and Preliminary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, several studies have shown that the isovalent doping into the Fe sublattice with trivalent cations having stable oxidation state, such as Ga or Al, enhance the stability of perovskite ferrite [16][17][18]. On the other hand, another work on Al-doped perovskite anodes for oxidation of hydrogen in IT-SOFC has been carried out [18].…”
Section: Introductionmentioning
confidence: 99%